Analisis Podcast Close The Door Tentang Pelanggaran Etika Episode Catheez - Iqbal Syaefulloh; Elsa Melinda; Raden Arla Syamira Putri; Samuel Tulus Hati Karo Karo; Ahmad Alfha Risi; Raihan Firdaus Naufal (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The purpose of this research is to conduct an analysis of possible ethical violations contained in the episode "CRAZY KAYA GINI TURNS OME TV⁉️ - CATHEEZ - WHERE IS THE BOCIL OME TV!?" from the "Close the Door" podcast narrated by Catheez. This research uses a qualitative approach to identify and evaluate ethical aspects that appear in the conversations and narratives in the podcast. This research also integrates feminist discourse theory with Vand DJik which is divided into 3 structures, namely macro structure, super structure and micro structure to explore the influence of this episode on gender construction and social norms in the context of conversation. The results of the research identified several forms of ethical violations which were emphasized in the episode  including gender stereotyping, verbal harassment, as well as the use of derogatory language. With a feminist discourse perspective, this research also reveals the ways in which these episodes may strengthen or undermine gender norms in society. The results of this research provide important insights regarding the influence of podcasts on understanding ethics and social norms, taking into account gender and feminist perspectives. This research makes an important contribution to understanding the ethical issues that arise in the world of podcasts and also how feminist discourse theory can be applied to analyze the impact of audio media such as podcasts in the social and cultural realm.